Performance Testing of Jute Fiber-Reinforced Composite Resin as a Crewboat Building Material - Mahadir Sirman; Henny Pasandang Nari; Syahrisal; Muhammad Arsyad Suyuti (Postgraduate, University of Mataram, 2025)
The maritime industry requires lightweight, strong, corrosion-resistant, and environmentally friendly materials, particularly for crewboat construction. Conventional metallic materials often suffer from corrosion, high weight, and elevated maintenance costs. This study investigates the mechanical performance of epoxy–jute fiber composite materials as a sustainable alternative for crewboat hull applications. Experimental laboratory testing was conducted using a quantitative approach to evaluate the tensile strength, flexural strength, impact resistance, and environmental durability of the composites. Specimens were fabricated using epoxy resin reinforced with jute fibers arranged in four different orientations (0°, 45°, 90°, and random) and tested according to ASTM standards. The results indicate that fiber orientation significantly influences mechanical properties. The 0° fiber orientation exhibited the highest tensile strength (89.04 MPa) and elongation (1.287%), indicating efficient load transfer and good ductility. The 45° orientation produced the highest flexural strength (39.14 MPa), while the random fiber orientation demonstrated the greatest elastic modulus (25.81 GPa) and impact resistance (6.409 kJ/m), providing superior stiffness and energy absorption. Seawater immersion tests showed no visible degradation in the composite structure. These findings suggest that epoxy–jute fiber composites have strong potential as eco-friendly crewboat construction materials, especially when applied using hybrid laminate configurations (0°/±45°/random) to optimize strength, stiffness, and impact resistance